Effects of hydroxyl radicals produced by a zinc phthalocyanine photosensitizer on tumor DNA. (February 2020) - Yan, Shufeng; Guo, Hanhan; Su, Jianqiang; Chen, Jincan; Song, Xiaorong; Huang, Mingdong; Zhang, Juncheng; Chen, Zhuo
Abstract: Photodynamic therapy (PDT) is a new therapeutic approach for cancer treatment. Its mechanism relies on three elements: photosensitizer, light and oxygen. Under aerobic conditions, a suitable wavelength of light activates the photosensitizer that results in the formation of reactive oxygen species (ROS). We herein report that PDT with a zinc phthalocyanine (ZnPc) photosensitizer coupled with 2, 4, 6-tris (N, N-dimethylaminomethyl) phenoxy (TAP), termed as ZnPc(TAP)4, has the ability to photodegrade DNA in tumor cells via hydroxyl radicals produced under the red light irradiation, resulting in effective elimination of tumor cells. Furthermore, the high-efficient anti-tumor effect of ZnPc(TAP)4 was verified in a human breast adenocarcinoma cell line MCF-7 tumor-bearing animal model. To the best of our knowledge, this is the first time that destructive effects of hydroxyl radicals produced by PDT on DNA of tumor cells has been documented, which may open up new avenues of antitumor therapy on eliminating the DNA of tumor cells.